Battery and liquid injection method thereof, energy storage device and power utilization system
By setting dimethyl carbonate in the electrolyte of lithium-ion batteries to limit its mass proportion, the problem of explosion risk in the process of thermal runaway is solved, and the safety performance and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411803152.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-11
AI Technical Summary
Lithium-ion batteries are prone to severe gas production and heat production during thermal runaway, resulting in combustion and explosion accidents in confined spaces, especially in large-scale energy storage applications.
Dimethyl carbonate (DMC) is provided in both the free and non-free electrolytes of the battery, and its mass ratio is limited to reduce the heat and gas released by the combustion of the electrolyte.
It effectively reduces the possibility of a battery explosion in thermal runaway test, while ensuring the safety performance and cycle life of the battery.
Smart Images

Figure BDA0005178760990000121 
Figure BDA0005178760990000131 
Figure BDA0005178760990000132
Abstract
Description
Technical Field
[0001] The present application belongs to the field of energy storage, and specifically relates to a battery and a liquid injection method thereof, an energy storage device and an electricity consumption system. Background Art
[0002] Lithium-ion batteries are widely used in the field of electrochemical energy storage due to their low cost and long life. However, thermal runaway is an inherent property of energy carriers, and its safety cannot be ignored, especially in large-scale energy storage applications.
[0003] For lithium-ion batteries, the thermal runaway process is accompanied by violent gas and heat generation, which can easily lead to safety accidents such as combustion and explosion in a confined space. Due to the small internal space and large capacity requirements of energy storage power stations, the large accumulation of gas and heat will lead to a higher risk of thermal runaway in lithium-ion batteries used for energy storage. Therefore, it is urgent to solve the thermal runaway problem of lithium-ion batteries.
[0004] In the related technologies, the methods to solve the thermal runaway problem of lithium-ion batteries for energy storage mainly include: improving the integration mode of battery cells and the design of structural parts to dredge exhaust, release pressure and prevent explosion; establishing fire accident warning through the thermal management system of the battery module box; improving the safety performance of lithium-ion batteries from the reaction source by improving the electrolyte, positive and negative electrodes, and diaphragms, etc. However, the above methods still cannot effectively solve the thermal runaway problem of lithium-ion batteries for energy storage. Summary of the invention
[0005] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a battery and its injection method, energy storage device and power system. The present application can effectively reduce the heat and gas released by the combustion of the electrolyte by setting dimethyl carbonate in both the free electrolyte and the non-free electrolyte, and respectively limiting the mass proportion of dimethyl carbonate, thereby effectively reducing the possibility of battery explosion in thermal runaway testing.
[0006] In a first aspect, the present application proposes a battery. According to an embodiment of the present application, the battery includes: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, the electrolyte includes a free electrolyte and a non-free electrolyte, the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet and an electrolyte in the pores of the separator; the free electrolyte includes dimethyl carbonate, and the mass proportion of dimethyl carbonate in the free electrolyte is m 1 %, the non-free electrolyte includes dimethyl carbonate, and the mass proportion of dimethyl carbonate in the non-free electrolyte is m 2 %, meet -5 <m 1 -m2 <0, and 20≤m 1 ≤45,30≤m 2 ≤50.
[0007] According to the battery of the above embodiment of the present application, by setting dimethyl carbonate (DMC) in both the free electrolyte and the non-free electrolyte, the heat and gas released by the combustion of the electrolyte can be effectively reduced, thereby effectively reducing the possibility of explosion of the battery in the thermal runaway test. At the same time, the present application limits the mass proportion of dimethyl carbonate (DMC) in the non-free electrolyte to 30% to 50%, which can not only effectively reduce the gas production and heat production of the electrolyte, but also effectively ensure the safety and other performance of the battery. The present application limits the mass proportion of dimethyl carbonate (DMC) in the free electrolyte to 20% to 45%, which can not only effectively slow down the occurrence of lithium precipitation during overcharging, but also has certain benefits for thermal runaway safety. At the same time, it can also ensure the smooth release of lithium ions from the positive and negative electrodes during the cycle process, significantly improve the cycle life of the battery, and also avoid the problems of seriously affecting the adhesion of the diaphragm and the cohesion of the pole piece due to the excessive content of dimethyl carbonate (DMC), deteriorating the safety performance and cycle performance of the battery. In addition, the present invention reduces the mass proportion of dimethyl carbonate (DMC) in the free electrolyte to m 1 % and the mass proportion of dimethyl carbonate (DMC) in the non-free electrolyte m 2 The difference is limited to -5% <m 1 -m 2 <0, ensuring that the mass proportion of DMC in the non-free electrolyte is higher than that in the free electrolyte, thereby maintaining sufficient DMC in the non-free electrolyte and bringing into play the advantages of DMC in heat and gas production as well as lithium ion conduction.
[0008] In addition, the battery according to the above embodiment of the present application may also have the following additional technical features:
[0009] In some embodiments of the present application, the bonding force between the separator and the negative electrode plate is S, satisfying 4N / m≤S≤33N / m.
[0010] In some embodiments of the present application, the electrolyte is formed by secondary injection, and the secondary injection includes a first injection of electrolyte and a second injection of electrolyte; the first injection of electrolyte includes dimethyl carbonate, and the mass proportion of dimethyl carbonate in the first injection of electrolyte is M 1 %, the two electrolytes include dimethyl carbonate, and the mass proportion of dimethyl carbonate in the two electrolytes is M 2 %, satisfying 25≤M 1 ≤45,0≤M 2 ≤20, M 2 / M 1 -m 1 / m 2 <0.
[0011] In some embodiments of the present application, 0.7m / N≤M is satisfied 1 / S≤9m / N,0≤M 2 / S≤5m / N.
[0012] In some embodiments of the present application, the diaphragm includes a diaphragm substrate and a ceramic coating arranged on at least one side of the diaphragm substrate, the thickness of the diaphragm substrate is 8μm to 20μm, the thickness of the ceramic coating on one side is 1μm to 3μm, the porosity of the ceramic coating is 30% to 50%, and the pore size of the pores in the ceramic coating is 0.05μm to 1μm.
[0013] The second aspect of the present application proposes a liquid injection method for a battery as described in the above embodiment. According to the embodiment of the present application, the liquid injection method includes:
[0014] Use one injection of electrolyte for the first injection, let it stand, and form;
[0015] Use two injections of electrolyte for the second injection, high temperature aging, and volume separation.
[0016] According to the injection method of the above embodiment of the present application, the electrolyte required for the battery formation stage and the electrolyte required for the circulation stage are separated by secondary injection, and the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery are flexibly controlled, which can effectively reduce the heat and gas released by the combustion of the electrolyte, thereby effectively reducing the possibility of battery explosion in thermal runaway testing.
[0017] In addition, the liquid injection method according to the above embodiment of the present application may also have the following additional technical features:
[0018] In some embodiments of the present application, the one injection of electrolyte includes dimethyl carbonate, and the mass proportion of dimethyl carbonate in the one injection of electrolyte is M 1 %, the two electrolytes include dimethyl carbonate, and the mass proportion of dimethyl carbonate in the two electrolytes is M 2 %, satisfying 25≤M1≤45, 0≤M 2 ≤20, M 2 / M 1 -m 1 / m 2 <0.
[0019] In some embodiments of the present application, a mass ratio of the first injection of electrolyte to the second injection of electrolyte is (6:4) to (8:2).
[0020] In some embodiments of the present application, the injection coefficient of the sum of the first injection of electrolyte and the second injection of electrolyte is 2.5 g / Ah to 5 g / Ah.
[0021] The third aspect of the present application proposes an energy storage device. According to an embodiment of the present application, the above energy storage device includes a battery of the above embodiment or a battery obtained by the injection method of the above embodiment. As a result, the energy storage device has excellent safety performance and cycle performance. It should be noted that the above-described features and advantages for the battery are also applicable to the energy storage device and will not be repeated here.
[0022] The fourth aspect of the present application proposes an electric power system. According to an embodiment of the present application, the electric power system includes: electric equipment, and an energy storage device as in the above embodiment, and the energy storage device supplies power to the electric equipment. As a result, the electric power system has excellent safety performance and cycle performance. It should be noted that the features and advantages described above for the battery are also applicable to the electric power system and will not be repeated here.
[0023] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0024] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.
[0025] In the first aspect of the present application, a battery is provided. According to an embodiment of the present application, the battery includes: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the separator is arranged between the positive electrode sheet and the negative electrode sheet, the electrolyte includes a free electrolyte and a non-free electrolyte, the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet and an electrolyte in the pores of the separator; the free electrolyte includes dimethyl carbonate (DMC), and the mass proportion of dimethyl carbonate (DMC) in the free electrolyte is m 1 %, the non-free electrolyte includes dimethyl carbonate (DMC), and the mass proportion of dimethyl carbonate (DMC) in the non-free electrolyte is m 2 %, meet -5 <m 1 -m 2 <0, and 20≤m 1 ≤45,30≤m 2≤50. Therefore, the present application can effectively reduce the heat and gas released by the combustion of the electrolyte by setting dimethyl carbonate (DMC) in both the free electrolyte and the non-free electrolyte, thereby effectively reducing the possibility of explosion of the battery in the thermal runaway test. At the same time, the present application limits the mass proportion of dimethyl carbonate (DMC) in the non-free electrolyte to 30% to 50%, which can not only effectively reduce the gas production and heat production of the electrolyte, but also effectively ensure the safety and other performance of the battery. The present application limits the mass proportion of dimethyl carbonate (DMC) in the free electrolyte to 20% to 45%, which can not only effectively slow down the occurrence of lithium precipitation during overcharging, but also has certain benefits for thermal runaway safety. At the same time, it can also ensure the smooth deintercalation of lithium ions between the positive and negative electrodes during the cycle, significantly improve the cycle life of the battery, and also avoid the problems of serious impact on the adhesion of the diaphragm and the cohesion of the pole piece due to the excessive content of dimethyl carbonate (DMC), deteriorating the safety performance and cycle performance of the battery. In addition, the present invention reduces the mass proportion of dimethyl carbonate (DMC) in the free electrolyte to m 1 % and the mass proportion of dimethyl carbonate (DMC) in the non-free electrolyte m 2 The difference is limited to -5% <m 1 -m 2 <0, ensuring that the mass proportion of DMC in the non-free electrolyte is higher than that in the free electrolyte, thereby maintaining sufficient DMC in the non-free electrolyte and bringing into play the advantages of DMC in heat and gas production as well as lithium ion conduction.
[0026] The principle of the beneficial effect of the battery proposed in this application is described in detail below:
[0027] The electrolyte of the battery of the present application includes a free electrolyte and a non-free electrolyte. The non-free electrolyte includes the electrolyte in the pores of the positive electrode plate, the electrolyte in the pores of the negative electrode plate and the electrolyte in the pores of the diaphragm, and the rest is a free electrolyte. Both the free electrolyte and the non-free electrolyte include dimethyl carbonate (DMC). The inventors found that compared with other types of organic solvents (such as ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc.), dimethyl carbonate (DMC) has lower gas production and heat production during thermal runaway. Overall, it has obvious advantages. Both the free electrolyte and the non-free electrolyte contain dimethyl carbonate (DMC), which can effectively reduce the heat and gas released by the combustion of the electrolyte, thereby effectively reducing the possibility of battery explosion in thermal runaway testing.
[0028] During the cycle or storage of the battery, when the SEI film of the positive active material in the positive electrode sheet and / or the negative active material in the negative electrode sheet is damaged, the non-free electrolyte will directly contact the positive and negative active materials, decompose to produce a large amount of gas and release a large amount of heat. Therefore, the dimethyl carbonate (DMC) content in the non-free electrolyte needs to reach a high content to minimize the gas production and heat production of the electrolyte. However, the dimethyl carbonate (DMC) content should not be too high, otherwise the non-free electrolyte lacks lithium salts and additives that can effectively repair the SEI film, and the interface protection layer is easy to fail under overcharge and overheating conditions, which is not conducive to the safety performance and other performance of the battery (such as cycle performance, storage performance, etc.). Therefore, the present application limits the mass proportion of dimethyl carbonate (DMC) in the non-free electrolyte to 30% to 50% (as an example, it can be 30%, 35%, 40%, 45%, 50%, etc.), which can effectively reduce the gas and heat production of the electrolyte and effectively ensure the safety performance and other performances of the battery.
[0029] In the embodiments of the present application, dimethyl carbonate (DMC) in the free electrolyte is a small molecule solvent, which performs well in lithium salt transmission capacity, so the free electrolyte contains enough dimethyl carbonate (DMC) to slow down the occurrence of lithium precipitation during overcharging to a certain extent, and it also has certain benefits for thermal runaway safety. At the same time, it can also ensure the smooth deintercalation of lithium ions between the positive and negative electrodes during the cycle, and significantly improve the cycle life of the battery. However, too much small molecule solvent dimethyl carbonate (DMC) will cause the swelling and dissolution of polymers in the battery core, such as accelerating the aging of materials such as PVDF, PP, and PE. Since the diaphragm, binder and other materials in the battery core are all polymers, they need to have long-term corrosion-resistant stability, so the content of dimethyl carbonate (DMC) in the free electrolyte should not be too high, otherwise it will seriously affect the adhesion of the diaphragm and the cohesion of the pole piece, and deteriorate the safety performance and cycle performance of the battery. Therefore, the present application limits the mass proportion of dimethyl carbonate (DMC) in the free electrolyte to 20% to 45% (as an example, it can be 20%, 25%, 30%, 35%, 40%, 45%, etc.), which can not only effectively slow down the occurrence of lithium precipitation during overcharging, but also have certain benefits for thermal runaway safety. At the same time, it can ensure the smooth deintercalation of lithium ions at the positive and negative electrodes during the cycle process, significantly improve the cycle life of the battery, and avoid the problems of seriously affecting the adhesion of the diaphragm and the cohesion of the pole pieces, and deteriorating the safety performance and cycle performance of the battery due to the excessive content of dimethyl carbonate (DMC).
[0030] In the embodiments of the present application, there is no absolute physical barrier between the non-free electrolyte and the free electrolyte in the battery cell. When the non-free electrolyte is insufficiently consumed, the free electrolyte is automatically absorbed by the capillary action of the pole piece and the diaphragm as a supplement. The electrolyte components of the two regions have dynamic differences during the cycle consumption process, so the component contents of the two regions also change dynamically during the use of the battery. 1 % and the mass proportion of dimethyl carbonate (DMC) in the non-free electrolyte m 2 The difference is limited to -5% <m 1 -m 2 <0, ensuring that the mass proportion of DMC in the non-free electrolyte is higher than that in the free electrolyte, thereby maintaining sufficient DMC in the non-free electrolyte and bringing into play the advantages of DMC in heat and gas production as well as lithium ion conduction.
[0031] In the embodiments of the present application, the closed-cell effect of the diaphragm when the battery cell is overheated can prevent the positive and negative electrodes from short-circuiting, effectively block the spread of heat, and improve thermal safety performance; at the same time, the good wettability of the diaphragm and the electrolyte provides a fast transmission channel for the electrolyte, avoiding problems such as lithium precipitation and by-product generation caused by electrolyte bridge breaking during the cycle, thereby improving the cycle performance. The present application limits the bonding force S between the diaphragm and the negative electrode plate to within the range of 4N / m≤S≤33N / m (as examples, it can be 4N / m, 7N / m, 10N / m, 15N / m, 20N / m, 25N / m, 30N / m, 33N / m, etc.), which can effectively promote the contact between the diaphragm coating and the active material layer of the electrode plate, make it easier for the electrolyte to be distributed to the surface of the negative electrode plate, make the SEI layer thin and uniform during the formation process, and greatly reduce the total consumption of the electrolyte; at the same time, it can also avoid the coating material on the diaphragm used to provide bonding force filling the pores of the negative electrode plate due to the excessively high S value, and a large number of micropores and mesopores form closed pores due to the lack of electrolyte, which causes ion channel bridge breaking and rapid cycle decay at the microscopic level.
[0032] According to some specific embodiments of the present application, the electrolyte is formed by secondary injection, and the secondary injection includes a first injection of electrolyte and a second injection of electrolyte; the first injection of electrolyte includes dimethyl carbonate, and the mass proportion of dimethyl carbonate in the first injection of electrolyte is M 1 %, the second electrolyte includes dimethyl carbonate, and the mass proportion of dimethyl carbonate in the second electrolyte is M 2 %, satisfying 25≤M 1 ≤45,0≤M 2 ≤20, M 2 / M 1 -m 1 / m 2 <0.
[0033] In the embodiments of the present application, one injection of electrolyte is used to generate the initial SEI film, and one injection of electrolyte is the portion remaining in the electrode and diaphragm pores after the formation reaction, forming a non-free electrolyte in the initial state. The second injection of electrolyte is used to supplement the electrolyte required for long circulation. When one injection of electrolyte is excessive, the portion that has not been consumed or has not entered the diaphragm and electrode pores merges with the second injection of electrolyte to form a free electrolyte in the initial state. The secondary injection flexibly controls the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery by separating the electrolyte required for the battery formation stage and the electrolyte required for the circulation stage.
[0034] In the embodiment of the present application, by reducing the mass proportion of dimethyl carbonate in a shot of electrolyte to M 1 % limited to 25≤M 1 ≤45, which can ensure that the mass proportion of dimethyl carbonate (DMC) in the non-free electrolyte is within the range of 30% to 50%, thereby effectively reducing the gas production and heat generation of the electrolyte and effectively ensuring the safety and other performance of the battery. 2 % limited to 0≤M 2 ≤20, which can ensure that the mass proportion of dimethyl carbonate (DMC) in the formed free electrolyte is in the range of 20% to 45%, thereby effectively slowing down the occurrence of lithium precipitation during overcharging, and also having certain benefits for thermal runaway safety. At the same time, it can also ensure the smooth deintercalation of lithium ions between the positive and negative electrodes during the cycle process, significantly improving the cycle life of the battery. In addition, it can also avoid the serious impact on the adhesion of the diaphragm and the cohesion of the pole piece due to the excessive content of dimethyl carbonate (DMC), and the deterioration of the safety performance and cycle performance of the battery.
[0035] In the embodiments of the present application, the diaphragm acts as a bridge for electrolyte transmission, and the diaphragm and the electrolyte work together to affect the cycle performance of the battery; the diaphragm is also a release medium for the heat and gas generated by the decomposition of the SEI film and the combustion of the electrolyte in the overcharge test, and the diaphragm and the electrolyte work together to affect the safety performance of the battery. Therefore, the present application limits the DMC content M in the first injection electrolyte and the second injection electrolyte. 1 、M 2 And the relationship between the adhesive force S between the separator and the negative electrode sheet satisfies 0.7m / N≤M 1 / S≤9m / N and 0≤M 2 / S≤5m / N, which is beneficial to reduce the generation of heat and gas during overcharging and is conducive to the release of heat and gas. At the same time, it can also avoid the inability to maintain self-repair of SEI film during the cycle due to the lack of bonding at the negative electrode interface.
[0036] In the embodiments of the present application, the first electrolyte and the second electrolyte further include other organic solvents, lithium salts, and additives, respectively. The above-mentioned other organic solvents include but are not limited to at least one of cyclic carbonates and their fluorinated compounds, linear carbonates and their fluorinated compounds, carboxylates and their fluorinated compounds. The use of the above-mentioned ester solvents has the advantages of a wide electrochemical window, a wide stable operating temperature range, and good electrical conductivity.
[0037] According to some specific embodiments of the present application, the diaphragm includes a diaphragm substrate and a ceramic coating arranged on at least one side of the diaphragm substrate, the thickness of the diaphragm substrate is 8μm to 20μm (as an example, it can be 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, etc.), the thickness of the single-sided ceramic coating is 1μm to 3μm (as an example, it can be 1μm, 2μm, 3μm, etc.), the porosity of the ceramic coating is 30% to 50% (as an example, it can be 30%, 35%, 40%, 45%, 50%, etc.), and the pore size of the pores in the ceramic coating is 0.05μm to 1μm.
[0038] As some specific embodiments, the membrane substrate may be a polyolefin substrate, which includes but is not limited to one of a polypropylene (PP) single-layer film, a polyethylene (PE) single-layer film, and a PP / PE / PP three-layer composite film. The polyolefin substrate has the advantages of excellent mechanical properties, excellent chemical stability, and relatively low cost.
[0039] As some further specific embodiments, the ceramic coating includes inorganic nanoparticles, and the inorganic nanoparticles include but are not limited to at least one of aluminum oxide, titanium dioxide, zirconium oxide, silicon oxide, antimony oxide, magnesium oxide, calcium carbonate and zeolite. As some further specific embodiments, the particle size of the inorganic nanoparticles can be 50nm to 200nm. The bonding interface between the ceramic coating and the polyolefin substrate is good and not easy to fall off, and the ceramic coating also improves the wettability of the electrolyte and the safety of the diaphragm, thereby ensuring the long cycle electrical performance and overcharge safety performance of the battery.
[0040] As some specific embodiments, the above-mentioned separator may further include an adhesive, including but not limited to at least one of vinylidene fluoride, ethyl acrylate, methyl acrylate, 2-methyl methacrylate and 2-ethyl methacrylate. The above-mentioned adhesive is used in combination with the ceramic coating in a variety of ways such as single-sided layered composite, single-sided single-layer composite, double-sided face composite, etc., which can further enhance the bonding force between the separator and the negative electrode.
[0041] It should be noted that the thickness, material, porosity, and pore size of the diaphragm substrate and ceramic coating mentioned above will affect the bonding force S between the diaphragm and the negative electrode plate.
[0042] In the embodiments of the present application, the above-mentioned battery can be used for both lithium-ion batteries and sodium-ion batteries. The following takes lithium-ion batteries as an example for explanation:
[0043] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, and the positive active material layer includes a positive active material. The specific type of the positive active material is not particularly limited. As some specific embodiments, the positive active material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium cobalt phosphate, lithium manganese phosphate, lithium nickel phosphate, lithium manganese oxide, binary materials, and ternary materials.
[0044] In some embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0045] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0046] In some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), polyhexafluoropropylene, and styrene-butadiene rubber (SBR).
[0047] In some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet (such as positive electrode active material, conductive agent, binder) are dispersed in an organic solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0048] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0049] In some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0050] In some embodiments of the present application, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. The silicon-based material may include at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin-oxygen compounds, and tin alloys.
[0051] In some embodiments of the present application, the negative electrode active material layer may further optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0052] In some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0053] In some embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0054] In some embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet (such as negative electrode active material, conductive agent, binder and any other components) are dispersed in an organic solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0055] The second aspect of the present application proposes a method for injecting liquid in a battery of one or more embodiments. According to the embodiments of the present application, the above-mentioned injection method includes: using one injection of electrolyte for the first injection, standing, and forming; using two injections of electrolyte for the second injection, high temperature aging, and capacity separation.
[0056] Specifically, the above-mentioned injection method includes:
[0057] S100: Use one injection of electrolyte for the first injection, let it stand, and form
[0058] In this step, an electrolyte is injected for the first time, left to stand, and formed to form an initial SEI film on the surface of the positive electrode active material and the negative electrode active material respectively. The part of the electrolyte remaining in the positive electrode plate, the negative electrode plate and the pores of the diaphragm after the electrolyte formation reaction forms a non-free electrolyte in the initial state.
[0059] S200: Second injection of electrolyte, high temperature aging, capacity division
[0060] In this step, two injections of electrolyte are used for the second injection, high temperature aging, and volume separation to form the initial state of free electrolyte. When one injection of electrolyte is excessive, the part that is not consumed or does not enter the pores of the diaphragm, positive electrode sheet, and negative electrode sheet merges with the second injection of electrolyte to form the initial state of free electrolyte.
[0061] According to the injection method of the embodiment of the present application, the electrolyte required for the battery formation stage and the electrolyte required for the circulation stage are separated by secondary injection, and the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery are flexibly controlled, which can effectively reduce the heat and gas released by the combustion of the electrolyte, thereby effectively reducing the possibility of battery explosion during thermal runaway testing.
[0062] In the embodiment of the present application, both the first and second electrolytes contain dimethyl carbonate. 1 % limited to 25≤M 1 ≤45, which can ensure that the mass proportion of dimethyl carbonate (DMC) in the non-free electrolyte is within the range of 30% to 50%, thereby effectively reducing the gas production and heat generation of the electrolyte and effectively ensuring the safety and other performance of the battery. 2 % limited to 0≤M 2 ≤20, which can ensure that the mass proportion of dimethyl carbonate (DMC) in the formed free electrolyte is in the range of 20% to 45%, thereby effectively slowing down the occurrence of lithium precipitation during overcharging, and also having certain benefits for thermal runaway safety. At the same time, it can also ensure the smooth deintercalation of lithium ions between the positive and negative electrodes during the cycle process, significantly improving the cycle life of the battery. In addition, it can also avoid the serious impact on the adhesion of the diaphragm and the cohesion of the pole piece due to the excessive content of dimethyl carbonate (DMC), and the deterioration of the safety performance and cycle performance of the battery.
[0063] In the embodiments of the present application, the electrolyte demand of the battery is related to the cell capacity, and the electrolyte demand can be represented by the injection coefficient (injection amount / cell capacity). According to some specific embodiments of the present application, the injection coefficient of the sum of the first injection of electrolyte and the second injection of electrolyte is 2.5g / Ah to 5g / Ah, and as an example, it can be 2.5g / Ah, 3g / Ah, 3.5g / Ah, 4g / Ah, 4.5g / Ah, 5g / Ah, etc. By limiting the injection coefficient within the above range, it can ensure that the diaphragm and the positive and negative electrode plates are fully infiltrated, and the electrolyte will not swell or accumulate at the bottom of the battery due to excessive amount of electrolyte, causing local lithium precipitation.
[0064] According to some further specific embodiments of the present application, the mass ratio of the first injection of electrolyte to the second injection of electrolyte is (6:4) to (8:2). By limiting the mass ratio of the first injection of electrolyte to the second injection of electrolyte within the above range, it can be ensured that the SEI protective layer formed by chemical formation is uniform and has good thermal stability, and the problem of overcharging thermal runaway can be effectively improved.
[0065] The third aspect of the present application proposes an energy storage device. According to an embodiment of the present application, the above energy storage device includes a battery of the above embodiment or a battery obtained by the injection method of the above embodiment. As a result, the energy storage device has excellent safety performance and cycle performance. It should be noted that the above-described features and advantages for the battery are also applicable to the energy storage device and will not be repeated here.
[0066] Specifically, the energy storage device of the present application may include but is not limited to a battery module, a battery pack, a battery system, etc. In addition, the energy storage device of the present application may also include at least one of an electric energy storage device for the power generation side of the power system, an electric energy storage device for the power distribution side of the power system (such as an electrochemical energy storage device), and an electric energy storage device for the user side of the power system.
[0067] The fourth aspect of the present application proposes an electric power system. According to an embodiment of the present application, the electric power system includes: electric equipment, and an energy storage device as in the above embodiment, and the energy storage device supplies power to the electric equipment. As a result, the electric power system has excellent safety performance and cycle performance. It should be noted that the features and advantages described above for the battery are also applicable to the electric power system and will not be repeated here.
[0068] The above-mentioned power consumption system may include but is not limited to mobile phones, tablet computers, laptop computers, desktop computers, smart bracelets, smart watches, e-readers, game consoles and other portable electronic devices. It may also include but is not limited to vehicles such as cars, trucks, cars, vans, motor vehicles, high-speed trains, electric vehicles, etc. In addition, it may also be various household appliances, such as but not limited to refrigerators, electric lights, air conditioners, etc.
[0069] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0070] Example 1
[0071] This embodiment provides a lithium ion battery, and the preparation method thereof includes:
[0072] 1) Preparation of positive electrode sheet:
[0073] The positive electrode active material is lithium iron phosphate (LiFePO 4 ), conductive carbon black (SP), and adhesive polyvinylidene fluoride (PVDF) are dispersed in a solvent N-methylpyrrolidone (NMP) in a mass ratio of 97:2.5:0.5 and mixed evenly to obtain a positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil. The coating weight per unit area of the positive electrode slurry is 33 mg / cm 2 After drying, cold pressing, slitting and cutting, the positive electrode sheet is obtained.
[0074] 2) Preparation of negative electrode sheet:
[0075] The negative electrode active material artificial graphite, conductive carbon black (SP), thickener (CMC) and binder (SBR) were dispersed in deionized water at a mass ratio of 96.5:0.5:1:2 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil. The coating weight per unit area of the negative electrode slurry was 16 mg / cm 2 After drying, cold pressing, slitting and cutting, the negative electrode sheet is obtained.
[0076] 3) Preparation of electrolyte:
[0077] In an argon atmosphere glove box with a moisture and oxygen content of ≤0.1ppm, other organic solvents EC:EMC were mixed at a mass ratio of 1:1, and DMC, lithium salts and additives were mixed according to the designed ratio in Table 1, and stirred until completely dissolved. The mass ratios of lithium salts and additives in the electrolyte were 12% lithium hexafluorophosphate, 3% lithium bis(fluorosulfonyl)imide, 3% vinyl carbonate, 0.5% fluoroethylene carbonate, 0.5% vinyl sulfate, and 0.5% tris(trimethylsilyl) phosphate.
[0078] The mass proportion of DMC in the first and second electrolytes is shown in Table 1. The total amount of other organic solvents decreases with the increase of the mass proportion of DMC (to ensure that the total amount of solvent remains unchanged), and the ratio of EC:EMC remains unchanged. The types and mass proportions of lithium salts and additive components in the first and second electrolytes are the same.
[0079] 4) Preparation of isolation membrane:
[0080] Commercially available aluminum oxide (Al2O3) with different coating thicknesses and substrate thicknesses were used. 2 O 3 ) coated diaphragm, the substrate is polyethylene (PE) film, and the bonding strength between different diaphragms and the negative electrode plate is used as the design value.
[0081] 5) Battery assembly:
[0082] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to separate the positive and negative electrode sheets, and then wound into a bare battery cell. After welding the pole ears, the battery cell is assembled into an outer package, and vacuum dried after hot pressing, and then a secondary liquid injection process is performed. Specifically, the first injection of electrolyte is performed, and the battery cell is packaged, left to stand, and formed; the second injection of electrolyte is performed, and the battery cell is left to stand at high temperature, and the capacity is tested, etc., and finally a soft-pack lithium-ion battery with a capacity of 3.2Ah is prepared.
[0083] The formation process adopts the following process: Step 1: the battery cell is allowed to stand in a 45°C formation cabinet for 10 minutes, and charged at a rate of 0.1C for 7 minutes to 1.17% SOC; Step 2: Stand for 3 minutes, and charge at a rate of 0.2C to 30% SOC.
[0084] Among them, the injection coefficient is 4.0g / Ah; the mass ratio of the first injection of electrolyte and the second injection of electrolyte is 7:3; the static conditions after the first injection are 45±5℃ for 24 hours, and the formation temperature is 45℃; the high temperature aging conditions after the second injection are 45±5℃ for 24 hours.
[0085] Embodiments 2 to 33
[0086] The preparation methods of Examples 2 to 33 are basically the same as those of Example 1, and the differences are detailed in Table 1.
[0087] Comparative Example 1
[0088] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0089] The traditional single injection method was adopted, and the specific parameters are shown in Table 1.
[0090] Comparative Examples 2-3
[0091] The preparation methods of Comparative Examples 2 to 3 are basically the same as those of Example 1, and the differences are detailed in Table 1.
[0092] The bonding force between the separator and the negative electrode plate, the free electrolyte components, and the non-free (pore) electrolyte components of the lithium ion batteries of Examples 1 to 33 and Comparative Examples 1 to 3 were tested respectively, and the results are shown in Table 1.
[0093] Adhesion test between the diaphragm and the negative electrode:
[0094] According to the national standard GB / T 2790-1995, the 180° peel test method is used to test the bonding force between the separator and the negative electrode. The fully dried separator and the negative electrode are flatly stacked together, and then the separator and the negative electrode are composited by hot pressing using a hot press. The hot pressing conditions are: temperature 90±0.2℃, pressure 1.2Mpa, hot pressing time 90±30s. The hot pressing temperature and hot pressing time are within the above range and have no effect on the effect of the embodiment. After the hot pressing is completed, the sample is cut into 15mm×50mm strips to test the bonding force S (N / m) between the separator and the negative electrode.
[0095] Free electrolyte composition test:
[0096] Discharge the battery with outer packaging with a current of 0.05C to 0% SOC (2.0V), cut a notch of about 0.5cm on the right side facing the positive column of the battery, and cut the same notch on the right side facing the negative column, ensuring that the two notches are on the diagonal line, and pour the free electrolyte into the fluoride bottle from the small opening on the side of the positive column until intermittent dripping flows down and count for 30s.
[0097] Gas chromatography-mass spectrometry (GC-MS) was used to test the types and relative mass contents of organic components in the collected electrolyte.
[0098] Non-free (pore) electrolyte composition test:
[0099] Remove the outer packaging, take out a single bare cell, quickly peel off the electrode, put it into an aluminum-plastic bag, add enough acetonitrile solvent to completely immerse the electrode, seal the aluminum-plastic bag containing acetonitrile solvent and electrode, and let it stand at 35±10℃ for 3 days.
[0100] Gas chromatography-mass spectrometry (GC-MS) was used to test the types and relative mass contents of organic components in the collected electrolyte.
[0101] Table 1
[0102]
[0103]
[0104] Thermal runaway tests and cycle tests were performed on the lithium ion batteries of Examples 1 to 33 and Comparative Examples 1 to 3, respectively. The results are shown in Table 2.
[0105] Refer to the national standard GB-T36276-2023 for lithium-ion battery performance testing, specifically:
[0106] Thermal runaway performance test:
[0107] In an environment with an initial temperature of 25±5℃, charge at a constant power of 0.5P until the trigger cell experiences thermal runaway or the trigger cell's state of charge reaches 200% SOC, and then stand and observe for 1 hour. During the test, collect the time, temperature, and voltage of the charging process.
[0108] After standing for 1 hour, the voltage of the battery cell is considered to have passed the thermal runaway test in a normal state, and explosion or fire is considered to have failed. From best to worst, they are passed, caught fire, and exploded, which is used to directly judge the effectiveness of the technology in improving thermal runaway. In comparison with the comparative example and the embodiment, which also passed, caught fire, or exploded, the lower the maximum temperature, the better the improvement effect.
[0109] Cycle performance test:
[0110] At 45℃, charge to 3.65V at 0.5P constant power, then discharge to 2.5V at 0.5P constant power. The capacity of the Xth cycle of charge and discharge is recorded as CC x 、DC x The energy of the Xth cycle of charge and discharge is recorded as CE x ,DE x , until X = 1000, record the capacity of each cycle. The battery cycle life is evaluated by the cycle capacity retention rate λ, λ = DC 1000 / DC 3 .
[0111] Table 2
[0112]
[0113]
[0114]
[0115] From Comparative Example 1, it can be seen that the difference in DMC content between the free electrolyte and the non-free electrolyte obtained by the traditional single injection method is very large. The enrichment degree of DMC in the non-free electrolyte is much higher than that in the free electrolyte. The test shows that it is easy to explode during overcharging, and the high-temperature cycle capacity retention rate is low, only 66%. Although Comparative Examples 2 and 3 use secondary injection, the mass proportion of DMC in the free electrolyte is m 1 % and the mass proportion of DMC in non-free electrolyte m2 % Not satisfied -5 <m 1 -m 2 <0. Tests show that explosion is likely to occur during overcharging, and the high-temperature cycle capacity retention rate is low.
[0116] It can be seen from Examples 1 to 10 that by adjusting the content of DMC in the first and second electrolytes, the design parameters can satisfy -5 < m 1 -m 2 <0, when the DMC content in the two electrolyte injections is kept unchanged, the thermal runaway and cycle test first improve and then deteriorate with the increase of the DMC content in one electrolyte injection. The optimal value is obtained in Example 5. 1 Too high, the lithium salt and additives required for film formation account for insufficient proportion. 1 When the DMC content in the first electrolyte is kept constant, the thermal runaway and cycle test are improved first and then deteriorated with the increase of the DMC content in the second electrolyte. The optimal value is obtained in Example 5. 2 Too high, DMC dissolves the polymer and causes aging and failure of the diaphragm and electrode adhesive. 2 Through Example 8, although the content of DMC and S value in the first and second electrolytes are strictly limited, its safety and cycle performance are not significantly improved compared with Comparative Example 1, which shows that m 1 -m 2 Most importantly, satisfy -5<m 1 -m 2 <0 is a key parameter to improve the cycle performance and safety performance of the battery.
[0117] It can be seen from Examples 11 to 15 that by adjusting the coating membrane substrate and the coating thickness, different membrane adhesion S values can be obtained. In Examples 5, 12 to 14, the S value satisfies 4N / m≤S≤33N / m. 1 -m 2 The influence is small. After adjusting the S value, the maximum temperature of the cycle and safety test is improved, but the safety test result is not greatly affected. In Example 11, S is too small, and in Example 14 and Example 15, S is too large, which has a great influence on m 1 -m 2 The impact is large, the cycle degradation is serious, and the safety performance deteriorates significantly when S is too small.
[0118] By comparing Example 16 and Example 6, it is found that by adjusting the membrane adhesion S value, m 1 -m 2As long as it still does not exceed the required range, the cycle performance of the battery can be further improved while ensuring that the thermal runaway test can pass and the national standard safety requirements are met. By comparing Example 17 and Example 7, it is found that by adjusting the DMC content in the secondary injection, m 1 -m 2 From not meeting the requirements to meeting them, the maximum temperature of the safety test can be significantly reduced and the cycle performance of the battery can be improved. By comparing Example 18 with Example 1, it is found that by comprehensively adjusting the DMC content and the adhesion of the diaphragm in the secondary injection, although the m 1 -m 2 , but m 1 -m 2 The requirements are still not met, and the battery safety performance and cycle performance tests are still not ideal.
[0119] It can be seen from Examples 19 to 21 that M 1 / S or M 2 / S has upper and lower limits. 1 / S or M 2 / S is too high, the negative electrode interface bonding is missing, weakening the SEI self-repair ability. 1 / S is too low, and a large amount of heat and gas are generated during overcharging and cannot be released.
[0120] It can be seen from Examples 23 to 28 that by limiting the injection coefficient of the sum of the primary injection electrolyte and the secondary injection electrolyte to a range of 2.5 to 5 g / Ah, the battery's cycle performance and thermal runaway test safety performance are both excellent, preferably 3.5 to 4.5 g / Ah.
[0121] It can be seen from Examples 29 to 32 that by limiting the mass ratio of the first injection of electrolyte to the second injection of electrolyte to within the range of (6:4) to (8:2), the battery's cycle performance and thermal runaway test safety performance are both excellent.
[0122] In Example 33, after adjusting the injection coefficient and the secondary injection mass ratio on the basis of Example 22, the thermal runaway test safety performance and the cycle capacity retention rate are further improved.
[0123] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0124] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A battery, characterized in that: Comprising: a positive electrode plate, a negative electrode plate, a separator, and an electrolyte, wherein the separator is disposed between the positive electrode plate and the negative electrode plate, the electrolyte includes a free electrolyte and a non-free electrolyte, and the non-free electrolyte includes the electrolyte in the pores of the positive electrode plate, the electrolyte in the pores of the negative electrode plate, and the electrolyte in the pores of the separator; the free electrolyte includes dimethyl carbonate, and the mass percentage of dimethyl carbonate in the free electrolyte is m1%, the non-free electrolyte includes dimethyl carbonate, and the mass percentage of dimethyl carbonate in the non-free electrolyte is m2%, satisfying -5 < m1 - m2 < 0, and 20 ≤ m1 ≤ 45, 30 ≤ m2 ≤ 50.
2. The battery according to claim 1, characterized in that The adhesion force between the separator and the negative electrode plate is S, satisfying 4 N / m ≤ S ≤ 33 N / m.
3. The battery according to claim 2, characterized in that The electrolyte is formed by secondary liquid injection, and the secondary liquid injection includes a first-injected electrolyte and a second-injected electrolyte; the first-injected electrolyte includes dimethyl carbonate, and the mass percentage of dimethyl carbonate in the first-injected electrolyte is M1%, the second-injected electrolyte includes dimethyl carbonate, and the mass percentage of dimethyl carbonate in the second-injected electrolyte is M2%, satisfying 25 ≤ M1 ≤ 45, 0 ≤ M2 ≤ 20, M2 / M1 - m1 / m2 < 0.
4. The battery according to claim 3, characterized in that Satisfying 0.7 m / N ≤ M1 / S ≤ 9 m / N, 0 ≤ M2 / S ≤ 5 m / N.
5. The battery according to any one of claims 1 to 4, characterized in that The separator includes a separator matrix and a ceramic coating provided on at least one side of the separator matrix, the thickness of the separator matrix is 8 μm to 20 μm, the thickness of the ceramic coating on one side is 1 μm to 3 μm, the porosity of the ceramic coating is 30% to 50%, and the pore diameter of the pores in the ceramic coating is 0.05 μm to 1 μm.
6. A method for injecting liquid into a battery as claimed in any one of claims 1 to 5, characterized in that: Comprising: Performing a first liquid injection with the first-injected electrolyte, standing, and forming. Performing a second liquid injection with the second-injected electrolyte, performing high-temperature aging, and grading.
7. The liquid injection method according to claim 6, characterized in that: The first-injected electrolyte includes dimethyl carbonate, and the mass percentage of dimethyl carbonate in the first-injected electrolyte is M1%, the second-injected electrolyte includes dimethyl carbonate, and the mass percentage of dimethyl carbonate in the second-injected electrolyte is M2%, satisfying 25 ≤ M1 ≤ 45, 0 ≤ M2 ≤ 20, M2 / M1 - m1 / m2 < 0.
8. The liquid injection method according to claim 6, characterized in that: The mass ratio of the first-injected electrolyte to the second-injected electrolyte is (6:4) to (8:2).
9. The liquid injection method according to claim 6, characterized in that: The injection coefficient of the sum of the first-injected electrolyte and the second-injected electrolyte is 2.5 g / Ah to 5 g / Ah.
10. An energy storage device, characterized in that: Comprising the battery according to any one of claims 1 to 5 or the battery obtained by the liquid injection method according to any one of claims 6 to 9.
11. An electricity system, characterized in that: Comprising: an electrical device, and the energy storage device according to claim 10, wherein the energy storage device supplies power to the electrical device.
Citation Information
Cited By
Battery and preparation method thereof
CN122051393A